"Shadow emperor" or "loyal paladin"? – The Janus face of previous owner involvement in family firm successions. Issue 1 (March 2018) - Ahrens, Jan-Philipp; Uhlaner, Lorraine; Woywode, Michael; Zybura, Jan
Abstract: Early research on succession in owner-led family firms described succession as a process of mutual role adjustment. This means the parallel lessening of the previous owner's involvement (POI) while a new generation family member gradually takes office as new CEO and owner. In this article, we analyze the performance impact of the frequent phenomenon of POI in the post-succession phase in owner-led family firms. Drawing on upper echelon theory and agency theory, we argue that POI is a two-sided strategy. We posit and test a comprehensive framework that integrates both positive and negative aspects of POI. Moreover, we show that whether POI radiates more salubrious than noxious effects to the family firm is highly context specific. Using 2SLS-IV regressions with multiple instruments to address a potential endogeneity of POI, we find that POI is positively related to performance when the successor's CEO-related human capital (i.e. CEO-related experience and education) is still limited, but turns negative with increased CEO-related human capital of the successor. Furthermore, we show that the performance effect of POI is linked to corporate age: it is positively associated with performance in younger firms, while this positive relation vanishes with increasing corporate age. We observe that both effects are amplified by the previous owner's discretion (i.e. the latitude of actions to shape organizational results) post-succession.